Security in Internet of Drones: A Comprehensive Review. Issue 1 (31st December 2022) - Samanth, Snehal; K V, Prema; Balachandra, Mamatha
Abstract: Unmanned Aerial Vehicles (UAVs), also called drones, are used for various applications with two basic classifications: civilian and military drones. Civilian drones are used for various applications like construction site monitoring, natural disaster area monitoring, agriculture, etc. Military drones are used for applications like monitoring a country's border, the transmission of information about the intruders to Ground Control Station (GCS), or to any other server which has been designed for the purpose. Before the real-time deployment of the Internet of Drones (IoD), the feasibility and efficiency of a proposed UAV framework should be tested in an open-source UAV simulator or any network simulator. AirSim simulator is an open-source UAV simulator that has different features like ease of development, efficient motion capture, efficient obstacle detections and collision detections, use of different sensor models, and physics models. Hence, a review has been done on recent UAV frameworks which have been designed and tested using the AirSim simulator. Since a vast amount of data is being transmitted between IoD devices in this era, there is a need for designing secure IoD communication frameworks, with the least compromise in the performance of the designed frameworks. Hence, an extensive review has been done on different secure IoD communication frameworks which have used different cryptography concepts like key agreement, authentication, encryption and decryption, integrity, blockchain, digital signatures, and have implemented their proposed frameworks in real-time, or by using network simulators. The common network simulators that have been used for simulating secure IoD frameworks/mechanisms are NS3 and OMNeT++.